Tackling the informal economy in the European Union: A social actor approach - Colin C. Williams; Aysegul Kayaoglu (UTMS Journal of Economics, 2016)
In recent years, participants in the informal economy have started to be viewed less as rational economic actors who engage in the informal economy when the pay-off is greater than the expected cost of being caught and punished, and more as social actors who engage when their tax morale (i.e., motivation to pay taxes) is low. To evaluate this new social actor approach and the implications for tackling the informal economy, this paper reports evidence from 41,689 face-to-face interviews conducted across the European Union. Multilevel logistic regression analysis reveals a strong association between participation in the informal economy and the level of tax morale. Finding that higher tax morale (and thus lower participation in the informal economy) is strongly correlated at the country-level with greater levels of state intervention and at the individual-level with characteristics such as gender, age, education and employment status, the outcome is to confirm a structuralist political economy explanation and refute the modernization and neo-liberal explanations and remedies, as well as to uncover the importance of some policy solutions not considered until now, including older citizens mentoring of younger people, and improving women's participation in the labour force.
Keywords: H26; J46; K42; O17; 330; informal economy; tax morale; modernization; political economy; European Union